Coloured Petri Nets and the Invariant-Method - Jensen, Kurt (DAIMI Report Series, 1983)
In many systems a number of different processes have a similar structure and behaviour. To shorten system description and system analysis it is desirable to be able to treat such similar processes in a uniform and succinct way. In this paper it is shown how Petri nets can be generalized to allow processes to be described by a common subnet, without losing the ability to distinguish between them. Our generalization, called coloured Petri nets, is heavily influenced by predicate/transition-nets introduced by H.J. Genrich and K. Lautenbach. Moreover our paper shows how the invariant-method, introduced for Petri nets by K. Lautenbach can be generalized to coloured Petri nets. Revised version (first version 1979)